(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Early childhood is a period of rapid development that occurs in the developmental aspect and has potential that must be developed. Early childhood education is education intended for those who are in the age range of 0-6 years. Portfolio assessment is one of the evaluation methods used to collect, analyze information about the development and abilities of early childhood through a collection of works or documents they produce. The purpose of this study was to analyze and describe the process of implementing portfolio assessment in group B of Efrata Medan Private Kindergarten, to identify the criteria and indicators used in portfolio assessment in group B of Efrata Medan Private Kindergarten, to analyze data obtained from artifacts and to understand child development in Efrata Medan Private Kindergarten. This study uses a qualitative approach, data collection techniques used Document Analysis, Interviews and Documentation. The results of the portfolio assessment study in the Efrata Medan Private Kindergarten group showed good results, this is indicated by the assessment can be carried out more consistently and precisely, based on the academic, social, and motoric progress of students and provide more in-depth reports to parents.